Simultaneous shape measurement and layers detection by means of low coherence interferometry and optical coherence tomography - Tomczewski, Slawomir; Pakula, Anna; Salbut, Leszek (Photonics Letters of Poland, 2012)
In this paper authors show the application of low coherence interferometry and optical coherence tomography with non-Gaussian light source, which are applicable in simultaneous measurement of micromembrane and detection of layers deposited on silicon wafer. The exemplary measurement results obtained with laboratory setup are presented. Full Text: PDF References D. Huang, et al. "Optical coherence tomography", Science, Vol. 254, 1178 (1991).CrossRef A. Dubois, L. Vabre, A.C. Boccara and E.l Beaurepaire, "High-Resolution Full-Field Optical Coherence Tomography with a Linnik Microscope", Appl. Opt. Vol. 41, 805 (2002).CrossRef J.W. Goodman, Statistical Optics (John Wiley & Sons 1985). A. Harasaki, J. Schmit and J.C. Wyant, "Offset of Coherent Envelope Position Due to Phase Change on Reflection", Appl. Opt. Vol. 40, 2101 (2001).CrossRef G. Kieran, J. Larkin, "Efficient nonlinear algorithm for envelope detection in white light interferometry", J. Opt. Soc. Am. A, Vol. 13, 832 (1996).CrossRef A. Hirabayashi, H. Ogawa and K. Kitagawa, "Fast Surface Profiler by White-Light Interferometry by use of a New Algorithm Based on Sampling Theory", Appl. Opt. Vol. 41, 4876 (2002).CrossRef J. Plucinski et al., "Optical low-coherence interferometry for selected technical applications", Bulletin of the Polish Academy of Sciences, Vol. 56, 155 (2008). DirectLink A. Pakula, L. Salbut, Fringe 2009, Springer, 358 (2009). S. Chen, A.W. Palmer, "Fringe order identification in optical fibre white-light interferometry using centroid algorithm method", Electronics Lett., Vol. 28, 553, (1992). CrossRef A. Sabac, C. Gorecki and M. Jozwkik, "Design, testing, and calibration of an integrated Mach-Zehnder-based optical read-out architecture for MEMS characterization", Proc SPIE, VOL. 5458, 141 (2004). DirectLink